What’s in a mugshot: visual characteristics newspaper media emphasize based on race and gender - Fahrny, Alayna R. (Kansas State University, 2016)
The media has a substantial role in providing knowledge about criminality to the public. Previous research has demonstrated that many media representations of crime and criminality perpetuate racial stereotypes and myths. The current study examines photographs in newspapers to investigate if a person of color has a higher chance of being presented by their mugshot over White individuals in crime stories. In addition the analysis examines how female offenders are presented in newspaper crime stories compared to men. To date, there has been no published research on the influence gender and race has on mugshot portrayals in newspaper media. The current study addresses this gap through an ethnographic content analysis of newspaper crime stories from widely circulated newspapers published between August 1, 2014 and October 31, 2014. The analyses are also informed by social constructionism and labeling theory.
Keywords: Photos; Stereotypes; Criminology